PENGARUH LOVING AROMATIC TOUCH FOR STUNTING RECOVERY (LATSR) TERHADAP ASUPAN ENERGI, WAKTU PULIH STATUS GIZI BALITA STUNTING - Fauziah Hanum Nur Adriyani (Health Sciences Journal, 2026)
Abstract Stunting remains a major public health problem in Indonesia and requires innovative, safe, and family-based interventions. Loving Aromatic Touch for Stunting Recovery (LATSR) combined with citronella oil is a non-pharmacological approach integrating loving touch and aromatherapy to improve appetite and nutritional recovery. This study aimed to analyze the effectiveness of LATSR compared with standard baby massage on energy intake, recovery time, and nutritional status of stunted children. A quasi-experimental pre–post design was conducted among 130 stunted children aged 24–59 months in Banyumas Regency, divided into LATSR (n=64) and baby massage groups (n=66). Variables measured included energy intake and recovery time after 12 weeks of intervention. Data were analyzed using paired tests, independent tests. The results showed that LATSR significantly increased energy intake (126.69%), feeding frequency (75%), and recovery time to normal nutritional status was faster in the LATSR group (11.25 days) than in the control group (26.47 days). LATSR with citronella oil is effective as a community-based intervention for accelerating nutritional recovery among stunted children. Keywords: stunting; loving aromatic touch; citronella oil; energy intake; recovery time Abstrak Stunting masih menjadi masalah kesehatan masyarakat di Indonesia dan memerlukan intervensi yang inovatif, aman, serta berbasis keluarga. Loving Aromatic Touch for Stunting Recovery (LATSR) dengan citronella oil merupakan intervensi non-farmakologis yang mengintegrasikan sentuhan penuh kasih dan aromaterapi untuk meningkatkan nafsu makan serta pemulihan status gizi. Penelitian ini bertujuan menganalisis efektivitas LATSR dibandingkan baby massage standar terhadap asupan energi, waktu pulih, dan status gizi balita stunting. Penelitian menggunakan desain quasi experiment pre–post pada 130 balita stunting usia 24–59 bulan di Kabupaten Banyumas, yang dibagi menjadi kelompok LATSR (n=64) dan baby massage (n=66). Variabel yang diukur meliputi asupan energi dan waktu pulih selama 12 minggu. Analisis data menggunakan uji berpasangan, uji tidak berpasangan. Hasil menunjukkan bahwa LATSR meningkatkan asupan energi sebesar 126,69% dan waktu pulih pada kelompok LATSR lebih cepat dibandingkan kelompok kontrol. LATSR efektif sebagai intervensi berbasis komunitas untuk percepatan pemulihan stunting. Kata kunci: stunting; loving aromatic touch; citronella oil; asupan energi; waktu pulih